2007
DOI: 10.1007/s00508-006-0726-7
|View full text |Cite
|
Sign up to set email alerts
|

Wirtschaftswachstum und die Inzidenz von Arbeitsunfällen in Österreich

Abstract: Economic development appears to have an impact on the incidence of occupational injuries in Austria. Health policy should emphasize the necessity for safety at work particularly in phases of economic slowdown.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 18 publications
0
17
0
Order By: Relevance
“…Barth et al examined the temporal relationship of injury rates and national income in a study with data from Austria. 23 The rate of injury declined as gross domestic product increased over the 50-year period from 1955 to 2004, and Barth et al concluded that economic development leads to improvements in occupational safety. 23 Most research on the impact of public policy on occupational injury rates in the United States has been directed toward policies that attempt to create incentives for employers to improve safety through regulation and enforcement or by adjusting insurance costs.…”
Section: Discussionmentioning
confidence: 99%
“…Barth et al examined the temporal relationship of injury rates and national income in a study with data from Austria. 23 The rate of injury declined as gross domestic product increased over the 50-year period from 1955 to 2004, and Barth et al concluded that economic development leads to improvements in occupational safety. 23 Most research on the impact of public policy on occupational injury rates in the United States has been directed toward policies that attempt to create incentives for employers to improve safety through regulation and enforcement or by adjusting insurance costs.…”
Section: Discussionmentioning
confidence: 99%
“…The main reason for this fact is in rising periods with the impact of general prosperity and increase in occupational health and safety measures due to the scientific and technological developments that create new opportunities for the prevention of these hazards and preventive security reduce work-related accidents. On the other hand, economic downturns coincide with job losses and decreasing investments, and fear of unemployment is known to be a risk factor for occupational accidents (Barth et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…employee health, work equipment used, long working hours, carelessness, fatigue, work organization, inability of the receipt of the safety precautions and safety training etc. As revealed in the study of economic growth and occupational injuries in Austria (Barth et al, 2007) many factors mentioned above are already related to overall economic development. It is expected that increasing the development level of a country ensures the social and economic rights of workers and the provision of decent job opportunities for employees.…”
Section: Introductionmentioning
confidence: 99%
“…Wiener Klinische (2007) [5] studied the relationship between decrease of occupational injury and economic growth in Austria and found that economic growth could decrease occupational injury. A Barth, R Winker, E Ponocny-Seliger, L Sögner (2007) [6] studied the relativity between gross domestic product (GDP) and occupational hurts by method of statistics analysis and found that there is close relationship between economic growth and the decrease of occupational hurts. WANG Xian-zhen et al (2007) [7] made a statistical research on 998 occupational safety and socioeconomic indexes in typical developed countries and China, and proved that occupational safety is related to socioeconomic development level on national level.…”
Section: Introductionmentioning
confidence: 99%